Bali is a battlefield Or the triumph of the imaginary over actuality - Mark Hobart (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The idea of Balinese culture as a unique, largely timeless, harmonious synthesis of religion, custom and art is remarkably resistant to historical and contemporary evidence to the contrary. Such a hegemonic vision, however imaginary, conveniently underwrites both local politics and tourism, and so national and global capitalism. Against this ideal of Bali-as-Paradise, a critical analysis suggests a quite different metaphor—Bali-as-a-battlefield—in many instances to be more appropriate and accurate. To understand why the Arcadian myth has proven so attractive to both Balinese and foreigners, we need to examine the work done by social imaginaries. Hypostatizing, essentializing, then mythologizing, a largely imaginary monolithic ‘Balinese culture’ delivers a docile population which not only accepts, but enthusiastically embraces, their increasing alienation and their subjection to the political and economic forces of capitalism.